2021
DOI: 10.3991/ijep.v11i1.15011
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Learning Ecosystem Using Digital Knowledge Engineering Through MOOCs Knowledge Repository System

Abstract: This paper presents the development of a learning ecosystem using digital knowledge engineering through a MOOCs knowledge repository system. This system comprises four parts: (1) Stakeholders, including instructors and learners; (2) A digital knowledge engineering learning process that describes the roles of instructors and learners, learning activities, and instructional tools; (3) A MOOCs knowledge repository system, which is the software de-veloped to enhance digital entrepreneurs’ competencies; and (4) Dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This result is in line with the idea that incorporating the gamification strategies of Landers' into the teaching process allows students to use their time more efficiently on the relevant task, which consequently leads to better student achievement scores [36]. As Thanachawengsakul and Wannapiroon stated, it is important to encourage online participation in order to provide online learning [37].…”
Section: Students' Achievementsupporting
confidence: 75%
“…This result is in line with the idea that incorporating the gamification strategies of Landers' into the teaching process allows students to use their time more efficiently on the relevant task, which consequently leads to better student achievement scores [36]. As Thanachawengsakul and Wannapiroon stated, it is important to encourage online participation in order to provide online learning [37].…”
Section: Students' Achievementsupporting
confidence: 75%
“…Content analysis was used to develop the conceptual framework of a MOOCs knowledge repository, and used a knowledge engineering process to enhance digital entrepreneur competencies [9]. It also developed a learning ecosystem that applied digital knowledge engineering through the MOOCs knowledge repository system [11] to describe the learning environment, and the roles of instructors and learners to enhance digital entrepreneur competencies. The research findings suggested that the MOOCs knowledge repository developed contained the following:…”
Section: Discussionmentioning
confidence: 99%
“…The system is compatible with all devices by connecting to the internet [6][7]10]. It consists of three modules: the user management module, the knowledge management module, and the report management module [8][9][10][11]…”
Section: Knowledge Repository Systemmentioning
confidence: 99%
See 2 more Smart Citations